Ten sessions of hyperbaric oxygen versus sham treatment in patients with long covid (HOT-LoCO): a randomised, placebo-controlled, double-blind, phase II trial - Kenny A Rodriguez-Wallberg; Judith Bruchfeld; Michael Runold; Peter Lindholm; Anders Kjellberg; Jan H Kowalski; Adrian Hassler; Sara El Gharbi; Sarah Al-Ezerjawi; Emil Boström; Marcus Ståhlberg; Malin Nygren-Bonnier; et al. (BMJ Open)
Objectives To evaluate if 10 sessions of hyperbaric oxygen treatments (HBOTs) improve short- and long-term health related quality of life, symptoms and physical performance in long covid patients compared with placebo.Design Parallel, randomised, placebo-controlled, double-blind trial.Setting Single-centre, university hospital, Sweden.Participants Previously healthy subjects aged 18–60 years, diagnosed with long covid were included. We excluded pregnant women, patients with RAND-36 (role limitations due to physical health (RP) and physical functioning (PF)) above 70, diabetes, hypertension and contraindications for HBOT.Interventions Subjects were randomly assigned to 10 sessions of HBOT or sham (placebo) treatments over 6 weeks. HBOT involved 100% oxygen, 2.4 bar, 90 min, placebo medical air, 1.34–1.2 bar. Randomisation (1:1) was done electronically, in blocks stratified by sex and disease severity. Subjects and investigators were blinded to allocation.Primary and secondary outcome measures Primary endpoints were changes from baseline in RAND-36 PF and RP at 13 weeks. Efficacy was analysed on an intention-to-treat basis. Harms were evaluated according to the actual treatment given.Results Between 15 September 2021 and 20 June 2023, 80 subjects (65 women, 15 men) were enrolled and randomised (40 in each group). The trial is completed. The primary endpoint analysis included 79 subjects (40 in HBOT and 39 in control). At 13 weeks, both groups showed improvement, with no significant difference between HBOT and placebo in PF (least square mean difference between groups (LSD), 0.63 (95% CI −7.04 to 8.29), p=0.87) and RP (LSD, 2.35 (95% CI −5.95 to 10.66), p=0.57). Harms: 43 adverse events (AEs), most commonly cough and chest pain/discomfort, occurred in 19 subjects (49%) of the HBOT group and 38 AEs in 18 subjects (44%) of the placebo group, one serious AE in HBOT and one death in the placebo group.Conclusions 10 HBOT sessions did not show more short-term benefits than placebo for long covid patients. Both groups improved, with a notable sex difference. HBOT has a favourable harm profile.Trial registration number ClinicalTrials.gov (NCT04842448), EudraCT (2021-000764-30). The trial was funded by Vetenskapsrådet (2022-00834), Region Stockholm (2020-0731, 2022-0674), Hjärt-Lungfonden and OuraHealth Oy.